A comparative study of rapid urease test and dilute carbol fuchsin staining technique for diagnosis of Helicobacter pylori infection - M., Saleem; R., Marudavanan; R., Gopal; shivekar, Sunil S; T., Mangaiyarkarasi (International Journal of Research in Medical Sciences, 2017)
Background: Helicobacter pylori (H.pylori) is a gram negative spiral bacilli associated with acid peptic disease (APD) and gastric carcinoma. A rapid urease test is the most common test performed for a quick clinical diagnosis with or without histopathological examination of antral biopsy specimens. Methods: In this study we evaluated the utility of a simple dilute carbol fuchsin stain (DCF) for identifying the spiral or curved forms of H.pylori in the direct smears of antral biopsy samples for diagnosis of H.pylori infection and compared the results with rapid urease test (RUT). Results: Sums of 100 cases were included in the study from which 61 (61%) were positive for urease production and shown typical spiral or curved bacilli by D.C.F stain. Conclusions: DCF stain was found to be an excellent stain for direct microscopic evaluation and compared well with RUT.